The Impact of a Hands-On Interventional Radiology Training Course on Radiology Resident's Training: A Single Academic Institution Experience - Nicholas Guimbarda; Hashim Armashi; William Parker; Arthur Freedman; Islam A.S. Elhelf (The Arab Journal of Interventional Radiology, 2023)
Purpose The aim of this study was to investigate the outcomes of an instructional hands-on training course that introduces radiology residents to the essential tools and skills needed to perform basic interventional radiology (IR) procedures.